1996
DOI: 10.1021/jp9602437
|View full text |Cite
|
Sign up to set email alerts
|

Complete Determination of Intermolecular Spectral Densities of Liquids Using Position-Sensitive Kerr Lens Spectroscopy

Abstract: Femtosecond position-sensitive Kerr lens spectroscopy is demonstrated to facilitate the direct and complete measurement of the third-order material response function, R (3) (t). The real parts of tensor element response, R 1111(3) (t) and R 1122 (3) (t), for liquid CS 2 have been measured and are quantitatively compared to the optical Kerr effect response, R 1221 (3) (t) + R 1212 (3) (t). The intermolecular Raman spectral densities are also obtained for each tensor element through Fourier transform. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 32 publications
3
20
2
Order By: Relevance
“…[13][14][15] In the so-called "position-sensitive Kerr lens" technique, developed by Simon et al, the deviation of a probe beam in the pumpinduced lens is measured by comparing the detected light in the two panels of a dual diode as a function of probe delay. 16,17 More recently, Gardecki et al 12 and Tokmakoff and co-workers 18,19 showed that placing an aperture in the probe beam path after the sample and adjusting the relative polarizations of the pump and probe beams allows to make a direct heterodyned detection of individual elements of the response function tensor, and developed an unified theory for all the TL techniques. This technique of spatially masked OKE ͑SM-OKE͒ allows measuring different components of the third-order response tensor that are not accessible by the OHD-OKE standard technique.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In the so-called "position-sensitive Kerr lens" technique, developed by Simon et al, the deviation of a probe beam in the pumpinduced lens is measured by comparing the detected light in the two panels of a dual diode as a function of probe delay. 16,17 More recently, Gardecki et al 12 and Tokmakoff and co-workers 18,19 showed that placing an aperture in the probe beam path after the sample and adjusting the relative polarizations of the pump and probe beams allows to make a direct heterodyned detection of individual elements of the response function tensor, and developed an unified theory for all the TL techniques. This technique of spatially masked OKE ͑SM-OKE͒ allows measuring different components of the third-order response tensor that are not accessible by the OHD-OKE standard technique.…”
Section: Introductionmentioning
confidence: 99%
“…As such, intermolecular modes continue to receive a great deal of attention in both experiment [1][2][3][4][5][6][7][8][9] and theory. [10][11][12][13][14][15][16][17][18] From an experimental standpoint, advances in laser technology have made possible the routine study of Raman-active intermolecular modes through stimulated spectroscopies, [19][20][21] which often offer distinct advantages over spontaneous spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] This was used to characterize relative temporal dynamics without measuring their absolute magnitude.…”
mentioning
confidence: 99%